Promotional effect of silver nanoparticles on the performance of N-doped TiO2 photoanode-based dye-sensitized solar cells - Lim, Su Pei; Pandikumar, Alagarsamy; Huang, Nay Ming; Lim, Hong Ngee; Gu, Guochen; Ma, Ting Li (Royal Society of Chemistry, 2014)
We report the first successful application of an N-TiO2–Ag nanocomposite as an efficient photoanode for highly efficient dye-sensitized solar cells (DSSC). The N-TiO2–Ag nanocomposites with different Ag contents were prepared using a simple chemical reduction method and characterized using various suitable techniques. The DSSC assembled with the N-TiO2–Ag-modified photoanode demonstrated an enhanced solar-to-electrical energy conversion efficiency of 8.15% compared to the photoanode of a DSSC composed of unmodified TiO2 (2.19%) under full sunlight illumination (100 mW cm−2, AM 1.5 G). This superior DSSC performance was due to the reduced band gap energy and retarded charge recombination that resulted from the introduction of plasmonic Ag nanoparticles on the surface of N-TiO2. The influence of the Ag content on the overall efficiency was also investigated, and the optimum Ag content for N-TiO2 was found to be 10 wt%. The enhanced solar energy conversion efficiency demonstrated by the N-TiO2–Ag nanocomposite makes it a promising alternative to conventional photoanode-based DSSCs.